Dekonstruksi Femininitas dalam Novel-novel Karya Eka Kurniawan: Dari Pekerjaan Sampai Kecantikan - Jaka Ahmad Zulkarnain; Wiyatmi - (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
One of the stereotypes of gender is femininity in which it is closely related to women. Femininity with passive characteristic is constructed to limit their moves. In Eka Kurniawan’s novels, the femininity is unstable. It brings an assumption that he is conducting the femininity deconstruction. This research is aimed to find out and to explain the femininity deconstruction in Eka Kurniawan’s novels. Three Eka Kurniawan’s novels were chosen as the data source of this research, they were Cantik Itu Luka, Lelaki Harimau, and Seperti Dendam, Rindu Harus Dibayar Tuntas. This research used critical discourse analysis method with post-modern feminism approach. There are seven forms of femininity deconstructions in Eka Kurniawan’s novels such as feminine jobs, feminine images, feminine habits, feminine symbols, feminine principles, feminine desire, and beauty. Femininity deconstruction shows that femininity has strengths and weaknesses. Femininity is conveyed and practiced either by men and women characters in his novels. Through femininity deconstruction, Eka Kurniawan draws images of how femininity is being deconstructed and how the characters in his novels questioning, rejecting, and or making use of femininity.